Perbandingan Nilai Galat Pada Model Penyakit Tuberkulosis Menggunakan Metode Euler dan Heun di DKI Jakarta - , Dwi Yulia Citra; Evelin Bunga Glorya; Khairunnisa Helmina; Lukita Ambarwati; Eti Dwi Wiraningsih (JMT (Jurnal Matematika dan Terapan), 2024)
This study aims to compare the error value of the tuberculosis disease model using the Euler method and the Heun method in DKI Jakarta. Tuberculosis (TB) remains a global health concern due to high prevalence rates in various regions, including DKI Jakarta. The Euler method and Heun method are two numerical techniques commonly used in modeling the spread of disease. Both methods were used to estimate the numerical solution of a mathematical model describing the spread of tuberculosis in DKI Jakarta. This study involves the use of recent epidemiological data to simulate and compare the prediction results between the Euler and Heun methods. The results showed a comparison of error values between the Euler and Heun methods in modeling the spread of tuberculosis disease in DKI Jakarta. The analysis of the difference in error values provides important insights in the selection of the most appropriate numerical method for modeling the spread of a complex disease such as tuberculosis.